Oceanographic Investigation of the Marginal Sea-Ice Zone of the Chukchi Sea--MIZPAC 74 - Paquette, Robert G; Bourke, Robert H (1976)
Continuous profiles of temperature and salinity (STD observations) were made in the shallow (approximately 45 m) Bering and Chukchi Seas in July 1974 as part of the MIZPAC program. In addition to measurements in ice-free waters, seven closely spaced crossings of the sea-ice margin were made along with two crossings of the Alaskan coastal zone. In all, 111 STD stations and approximately 100 XBT drops were made for which graphs and tabulations were produced of temperature, salinity, density and sound speed. South of the ice the water is sharply layered with a warm fresh layer (8-10 C and approximately 10m thick) above a cold dense layer. At or near the sea-ice margin the layering gradually disappears with modification of isopycnals and isotherms extending to the bottom. Large scale temperature fluctuations of 0.5 to 2 C, termed mesostructure, were observed at 12-15m depth in the first three crossings, but were weak or absent in the other crossings. Mesostructure appears to be correlated with a relatively rapid melting of the ice, and hence, probably with a strong northward flow, or a diffuse ice margin . Mesostructure formation is believed to result from non-uniform lateral mixing of waters of different temperatures but the same density, possibly modified or controlled by a complex lateral pressure field near the ice. Presented at the Fall Annual Meeting of the American Geophysical Union, 10 Dec 1975, San Francisco, CA. Master's thesis.